DICER1 RNase IIIb domain mutations trigger widespread miRNA dysregulation and MAPK activation in pediatric thyroid cancer - Ricarte-Filho, Julio C.; Casado-Medrano, Victoria; Reichenberger, Erin; Spangler, Zachary; Scheerer, Michele; Isaza, Amber; Baran, Julia; Patel, Tasleema; MacFarland, Suzanne P.; Brodeur, Garrett M.; Stewart, Douglas R.; Baloch, Zubair; et al. (Frontiers in Endocrinology, 2023)
DICER1 is a highly conserved RNase III endoribonuclease essential for the biogenesis of single-stranded mature microRNAs (miRNAs) from stem-loop precursor miRNAs. Somatic mutations in the RNase IIIb domain of DICER1 impair its ability to generate mature 5p miRNAs and are believed to drive tumorigenesis in DICER1 syndrome-associated and sporadic thyroid tumors. However, the DICER1-driven specific changes in miRNAs and resulting changes in gene expression are poorly understood in thyroid tissue. In this study, we profiled the miRNA (n=2,083) and mRNA (n=2,559) transcriptomes of 20 non-neoplastic, 8 adenomatous and 60 pediatric thyroid cancers (13 follicular thyroid cancers [FTC] and 47 papillary thyroid cancers [PTC]) of which 8 had DICER1 RNase IIIb mutations. All DICER1-mutant differentiated thyroid cancers (DTC) were follicular patterned (six follicular variant PTC and two FTC), none had lymph node metastasis. We demonstrate that DICER1 pathogenic somatic mutations were associated with a global reduction of 5p-derived miRNAs, including those particularly abundant in the non-neoplastic thyroid tissue such as let-7 and mir-30 families, known for their tumor suppressor function. There was also an unexpected increase of 3p miRNAs, possibly associated with DICER1 mRNA expression increase in tumors harboring RNase IIIb mutations. These abnormally expressed 3p miRNAs, which are otherwise low or absent in DICER1-wt DTC and non-neoplastic thyroid tissues, make up exceptional markers for malignant thyroid tumors harboring DICER1 RNase IIIb mutations. The extensive disarray in the miRNA transcriptome results in gene expression changes, which were indicative of positive regulation of cell-cycle. Moreover, differentially expressed genes point to increased MAPK signaling output and loss of thyroid differentiation comparable to the RAS-like subgroup of PTC (as coined by The Cancer Genome Atlas), which is reflective of the more indolent clinical behavior of these tumors.